2010
DOI: 10.1016/j.ijfoodmicro.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Food-borne diseases — The challenges of 20years ago still persist while new ones continue to emerge

Abstract: The burden of diseases caused by food-borne pathogens remains largely unknown. Importantly data indicating trends in food-borne infectious intestinal disease is limited to a few industrialised countries, and even fewer pathogens. It has been predicted that the importance of diarrhoeal disease, mainly due to contaminated food and water, as a cause of death will decline worldwide. Evidence for such a downward trend is limited. This prediction presumes that improvements in the production and retail of microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
709
2
40

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,032 publications
(755 citation statements)
references
References 58 publications
4
709
2
40
Order By: Relevance
“…La contaminación puede deberse a la deficiencia en el proceso de elaboración, manipulación, conservación, transporte, distribución o comercialización de alimentos y agua, las cuales pueden clasificarse en infecciones o intoxicaciones alimentarias sin incluir las reacciones de hipersensibilidad a los alimentos (1)(2)(3) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La contaminación puede deberse a la deficiencia en el proceso de elaboración, manipulación, conservación, transporte, distribución o comercialización de alimentos y agua, las cuales pueden clasificarse en infecciones o intoxicaciones alimentarias sin incluir las reacciones de hipersensibilidad a los alimentos (1)(2)(3) .…”
Section: Introductionunclassified
“…Las ETA son una causa importante de morbilidad y mortalidad en todo el mundo, además de producir un gran impacto económico tanto por los gastos en salud producidos como en las actividades económicas relacionadas con la producción de alimentos (2)(3)(4)(5) . Para el año 2005 se estimó que 1,5 millones de personas murieron a causa de enfermedades diarreicas a nivel mundial y el 70% de ellas son atribuidas a las ETA (5) .…”
Section: Introductionunclassified
“…According to them the highest rate of contamination was by Klebsiella spp 09 (40.9%), followed by S. aureus 07 (31.8%), and E. coli 06 (27.27%). Various reports from all over the world revealed that bacterial foodborne agents have been the most well investigated and monitored causes of intestinal infectious disease and food-borne bacteria are increasingly becoming resistant to antimicrobials (12)(13)(14). Among these bacteria, Staphylococcus spp have been known to cause Staphylococcal food poisoning due to ingestion of improperly stored food in which Staphylococcous aureus has grown.…”
Section: Discussionmentioning
confidence: 99%
“…7 There are over 200 known microbial, chemical, or physical agents that can cause foodborne illness. 6 CDC estimates that of all the foodborne infections, 44% of the hospitalizations and deaths are attributed to 31 known pathogens. 7 In light of this serious public health crisis, efforts have been directed toward the detection, control, and prevention of food-borne pathogens and diseases.…”
Section: Introductionmentioning
confidence: 99%